Business cycles, economic crises, and the poor : testing for asymmetric effects - Agénor, Pierre-Richard, 1957- 1957- (Policy research working paper, 2001)
Analysis of data from Brazil suggest that poverty responds asymmetrically to output shocks, showing less tendency to fall in response to a positive shock when the economy is initially in a downturn